Evaluasi program pelatihan in-house training pembelajaran paket C di sanggar kegiatan belajar Jawa Tengah - Ika Rizqi Meilya; Ibnu Syamsi (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2015)
Tujuan penelitian ini adalah mendeskripsikan hasil evaluasi tingkat: (1) kepuasan; (2) pemahaman materi; (3) implementasi perilaku; dan (4) peningakatan kompetensi peserta pelatihan. Jenis penelitian ini adalah penelitian evaluasi menggunakan model Empat Level Kirkpatrick. Hasil penelitian menunjukkan: (1) kepuasan peserta terhadap penyelenggaraan pelatihan menggunakan Penilaian ber-Acuan Patokan (PAP) dan Penilaian ber-Acuan Norma (PAN) masuk kategori “puas”. (2) pemahaman peserta pada materi standar isi pembelajaran paket C menggunakan PAP masuk kategori “tidak menguasai”, sedangkan menggunakan PAN masuk kategori “menguasai”; pemahaman peserta pada materi standar proses pembelajaran paket C menggunakan PAP dan PAN masuk kategori “menguasai”; pemahaman peserta pada materi standar penilaian pembelajaran paket C menggunakan PAP masuk kategori “tidak menguasai”, sedangkan menggunakan PAN masuk kategori “menguasai”. (3) implementasi perilaku peserta pascapelatihan terkait materi standar isi, proses, dan penilaian pembelajaran paket C berdasarkan persepsi tutor dan peserta didik menggunakan PAP dan PAN masuk kategori “mengimplementasikan”; (4) peningkatan kompetensi peserta disebabkan oleh pelatihan menggunakan PAP dan PAN masuk kategori “mengalami peningkatan”.Kata Kunci: evaluasi, pelatihan, in-house training, pembelajaran paket C In-house training program evaluation of packet C learning in sanggar kegiatan belajar of Central Java ProvinceAbstractThis study aimed to describe an evaluation results level of: (1) satisfaction; (2) material understanding; (3) behavior implementation; and (4) the improvement of participants’ competence. The type of this study was evaluation research using Four Levels of Kirkpatrick model. The result of this study indicates the following. (1) the participants’ satisfaction toward the implementation of training using Standard Referenced Assessment (PAP) and Normative Referenced Assessment (PAN) was included in the category of “satisfied”. 2) the participants’ understanding of content standard material learning using PAP was included in the category of “not mastering”, while using PAN was included in the category of “mastering”; the participants’ understanding of process standard material learning using PAP and PAN was included in the category of “mastering”; (3) the participants’ understanding of assessment standard material learning using PAP was included in the category of “not mastering”, while using PAN was included in the category of “mastering”. (3) the implementation of participants’ behavior after training of content, process, and assessment standard material based on tutor’s and student’s perception using PAP and PAN was included in the category of “implementing”. (4) participants’ competence improvement resulting from the training using PAP and PAN was included in the category of “improving”. Keywords: evaluation, training, in-house training, packet C learning